ASSOCIATION OF MID UPPER ARM CIRCUMFERENCE AND COGNITION: A POPULATION-BASED COHORT STUDY. (20th December 2022) - Lynch, David; Howard, Annie Green; Tien, Hsiao-Chuan; Du, Shufa; Zhang, Bing; Wang, Huijun; Gordon-Larsen, Penny; Batsis, John
Abstract: Introduction: Evidence suggests a positive association between muscle mass and cognitive impairment exists. Mid-upper arm muscle circumference (MUMC) is a simple measure that may provide prognostic information on cognitive status. Methods: We included adults aged ≥55 years from the China Health and Nutrition Survey 1997-2018 with MUAC and triceps skinfold (TSF) measurements at each visit. Cognition was estimated based on a subset of the modified Telephone Interview for Cognitive Status (TICS, 0─27). Sex-stratified linear mixed-effects models accounting for within-individual and within-community correlation assessed the association between MUAC and the ratio of MUAC:TSF with TICS across age. We tested whether the rate of cognitive decline by age differed by quartiles of MUAC and MUAC:TSF in separate models. In cases of no statistical differences in cognitive declines by age, we tested whether overall cognitive function was associated with quartiles of MUAC and MUAC:TSF across all ages. Results: Of 5, 964 adults (53% female, age 62.4±6.4), mean MUAC was 26.6±3.74 and 26.2±3.9 cm, mean MUAC:TSF ratio was 2.9±1.6 and 1.94±1.1, and baseline TICS was 15.4±6.1 and 13.2±6.4 for men and women, respectively. MUAC was not associated with the rate of cognitive decline. Lower MUAC was associated with higher overall cognitive function scores for men (p=0.01) and women (p=0.05). For men and women there was no association between MUAC:TSF ratio and either cognitive decline or overall function. Conclusion: MUMC can be a marker to predict overall cognitive function across this period in the lifecycle, suggesting that declining MUAC may help predict lower overall cognitive function